A concise perspective on the effect of interpreting the double layer capacitance data over the intrinsic evaluation parameters in oxygen evolution reaction. (April 2023) - Karmakar, Arun; Kundu, Subrata
Abstract: Electrochemical active surface area (ECSA) normalized polarization information of an electrocatalyst provide an insightful information of specific activity. ECSA values of a catalyst are directly related to the double-layer capacitance (Cdl ) value of the catalyst. Here in this report, we have highlighted the effective ways of calculating Cdl values for the determination specific OER activity in detail. Various electrochemical analysis shows that selection of proper ways of calculating Cdl values can direct us to get real and error-free specific activity information. From the experimental verification, it is observed that linear fitting (LF) method can be a best practice for providing much more reliable data as compare to normal slope calculation (NSC) to get Cdl value of a catalyst. Obviously, it is common to expect that the Cdl value obtained from both methods should provide same value. But adopted internal unit conversion during the calculation of Cdl by NSC method could bring a severe error. Using our critical valuations of Cdl data followed by the specific activity, per-site TOF, surface area and surface coverage information researchers can ensure precision and correctness when presenting their data regarding the activity of an electrocatalyst. Graphical abstract: Image 1 Highlights: The effect of Cdl values on the intrinsic activity of a OER catalyst have discussed here. Mis-interpretation of Cdl value could bring an error in the scale of 10 3 . Effect over per-site TOF has discussed in details. The significance of employing linear fitting in determining the Cdl value is shown.